Al-Quran Sebagai Trauma Healer Bagi Masyarakat Korban Gempa Bumi dan Likuifkasi di Kota Palu - Darlis; Jusmiati; Ahmad Sehri bin Punawan; Tamrin Talebe (Al-Ulum, 2020)
This article focuses on the elaboration of the Qur'anic phenomenon as a trauma healer for victims of the disaster such as earthquake, tsunami, and liquefaction in Palu. The research method used interviews and direct observation with victims. This article aims to elaborate on the Quran's phenomenon as a trauma healer that is very effective in overcoming trauma for victims of natural disasters in Palu. The findings of this article show that when earthquake victims experience fear, sadness, and insomnia, they undergo healing trauma independently through reading (tartil), hearing (tasmi'), and recollecting (tadabbur) verses of the Koran. The research shows that people's reception of the Quran is very dynamic. The Quran's miracles are not limited to legal aspects, language, and future information, but it also on an excellent aspect (tartil), which can comfort the heart and increase the spirit of life for people affected by a disaster.